A practical guide to personal conditioning - Peterson, David D. 1972- EdD., CSCS*D; Rittenhouse, Melissa A. PhD, RD, CSSD (Jones & Bartlett Learning, 2019)
A Practical Guide to Personal Conditioning concisely and comprehensively connects the science of exercise with real-world application to sport and human performance, providing readers with both the "why" and "how" behind effective exercise prescription and programming. This engaging text explores the Information necessary to develop an exercise and nutrition plan specifically designed and tailored to fit their personal fitness goals. It also encourages the reader to consider the numerous factors that may impact or complicate their plan, including the physical demands of readers' activities, environmental factors, and nutritional requirements. Anchored in exercise science, the authors have striped to present a safe and scientific approach to exercise prescription, programming, and nutrition